Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Xiaomi Studi Pada Mahasiswa FEB Unisma Prodi Manajemen Angkatan 2019 - Roisul Am, Moch Izza; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to; (1) Know and analyze the impact of product quality and price on Xiaomi customer satisfaction. (2) Analyze the impact of product quality on individual Xiaomi customer satisfaction (3) Know and analyze the impact of price on Xiaomi customer satisfaction.This research method is Questionnaire (questionnaire) This method is used to collect data on product quality and price on customer satisfaction. The sampling technique used in this study is a probability technique by means of random sampling (Simple Random Sample Method), namely by a sample selection method in which each member of the population has the same opportunity to be selected as a sample member. In analyzing this method, the author uses the formula of the slovin formula, it can be determined that the number of samples is 86 respondents from 598 total students of the Islamic University of Malang. Keywords : Consumer Satisfaction, Product Quality, Price